La perspectiva de género y las relaciones sociales entre las mujeres y los hombres - MSc. Yomara Peña-Martínez (Santiago, 2015)
This article is a theoretical reflection that intends to analyze the utility of the gender perspective in the understanding of the social relationships between women and men. In function of this, was made a revision of documents about the thematic of gender, using as theoretical methods the analysis, the synthesis and the historical-logical one. It is commented on the concept of gender, its distinction with the term sex and its implications to relocate the biological and sociocultural aspects inside the explanations on femininity, masculinity and the links among them. It is concluded that the gender perspective has allowed making visible the ways in that the sexual difference has been as pretext to produce unequal relationships between women and men, in the context of gender socialization process.